2017
DOI: 10.14254/2071-789x.2017/10-3/6
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities in Labor Force Migration abroad in Slovak Republic and in Czech Republic

Abstract: ABSTRACT. We find it interesting and useful to examine regional differences in labor force and here we focus on the comparison of regional differences in Slovakia and Czech Republic, the countries that are very close in terms of population mentality and way of life. A significant share of highly skilled labor force in both countries in question leaves homes, thus external migration. Labor force is beginning to be a serious problem for both economies. In this study our objective is to evaluate and compare regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As for Ukraine, the emigration in which is the subject of the study in this article, we revealed the corresponding reasons as well as their interrelation with socioeconomic basis of migration decisions in our preceding papers (Bilan, 2017;Mishchuk & Grishnova, 2015;Mishchuk et al 2018) and some other researches (Cohen, 2017;D'Silva & Samah, 2018;Holovatyi, 2014;Máté et al, 2018). At the same time, Ukrainian scientists, like their European counterparts who are studying the problem of brain gain in favour of more developed countries, for instance (Grenčíková et al 2017), are trying to find a common solution for all source countries in order to transform the process of intellectual migratory losses into the brain circulation and justify the policy measures that can enforce the benefits of circulation of knowledge and skills (Bilan & Bilan, 2011;Puraite et al, 2017;Sadova, 2010;Semiv & Hvozdovych, 2012;Stakanov, 2018).…”
Section: Literature Reviewmentioning
confidence: 52%
“…As for Ukraine, the emigration in which is the subject of the study in this article, we revealed the corresponding reasons as well as their interrelation with socioeconomic basis of migration decisions in our preceding papers (Bilan, 2017;Mishchuk & Grishnova, 2015;Mishchuk et al 2018) and some other researches (Cohen, 2017;D'Silva & Samah, 2018;Holovatyi, 2014;Máté et al, 2018). At the same time, Ukrainian scientists, like their European counterparts who are studying the problem of brain gain in favour of more developed countries, for instance (Grenčíková et al 2017), are trying to find a common solution for all source countries in order to transform the process of intellectual migratory losses into the brain circulation and justify the policy measures that can enforce the benefits of circulation of knowledge and skills (Bilan & Bilan, 2011;Puraite et al, 2017;Sadova, 2010;Semiv & Hvozdovych, 2012;Stakanov, 2018).…”
Section: Literature Reviewmentioning
confidence: 52%
“…These can be translated by the decreasing labor force in the emerging economies, which prefer to leave the country of their origin for various reasons, especially related to the higher net income, received in the host country. At this conclusion reached also Grenčíková et al. (2017).…”
Section: Empirical Results and Discussionmentioning
confidence: 73%
“…However, the fiscal effects are low. On the other hand, the decision to emigrate is largely influenced by the net income expected in the host country (Grenčíková et al, 2017;Streimikiene et al, 2016). Taxation in the origin country versus taxation in the host country may influence the migration decision, but according to Haapanen & Ritsila (2001) its amplitude depends on the age of the individual, regional unemployment rate and level of net earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the result of natural, technical, educational, public, economic and socio-cultural processes, by which a complex is created being connected with internal relations. (Cseh Papp, Varga, Schwarczová, & Hajós, 2018;Kádár, 2017) Each region is influenced by many heterogeneous factors that contribute to its development: factor of region's location; the factor of territorial-administrative division; factor of the settlement hierarchy; factor of economic development progress; factor of the political situation; localization of enterprises; the factor of foreign direct investment (Fabuš & Csabay 2018); factor of innovation processes; factor of the specificity of demographic structures and its mobility (Grenčíková, Španková, & Habánik, 2017;Vlacseková & Mura, 2017); production factors (Koišová, Masárová, & Habánik, 2018); quantitative and qualitative characteristics of the population and its movement (Ďurková, Čábyová, & Vicenová, 2012); research and development (Duľová Spišáková, Mura, Gontkovičová, & Hajduová, 2017) and others. The factor of human resources also belongs to these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Many regions produce strategic regional competitiveness in which the development of human resources figures prominently. Over the years, the results of various studies (Grenčíková, et al, 2017;Chocholatá & Furková, 2018;Jeřábek, 2016;Kádár, 2017;Laskowska & Dańska-Borsiak, 2016;Oremusova, 2010;Pavel & Jucu, 2018;Silin & Tkacheva, 2015;Srovnalíková, Gruzauskas, & Navickas , 2016;Yussof & Kasim, 2003) proposed the indicators by which it is possible to assess the level of regional development influenced by human resources from various perspectives.…”
Section: Introductionmentioning
confidence: 99%